Biochemical, structural and functional diversity between two digestive alpha-amylases from helicoverpa armigera - Bhide, Amey J.; Channale, Sonal M.; Patil, Sucheta S.; Gupta, Vidya S.; Ramasamy, Sureshkumar; Giri, Ashok P. (Biochimica Et Biophysica Acta-General Subjects, 2015)
Background: Helicoverpa armigera (Lepidoptera) feeds on various plants using diverse digestive enzymes as one of the survival tool-kit. The aim of the present study was to understand biochemical properties of recombinant alpha-amylases of H. armigera viz., HaAmy1 and HaAmy2. Methods: The open reading frames of HaAmy1 and HaAmy2 were cloned in Pichia pastoris and expressed heterologously. Purified recombinant enzymes were characterized for their biochemical and biophysical attributes using established methods. Results: Sequence alignment and homology modeling showed that HaAmy1 and HaAmy2 were conserved in their amino acid sequences and structures. HaAmy1 and HaAmy2 showed optimum activity at 60 degrees C; however, they differed in their optimum pH. Furthermore, HaAmy2 showed higher affinity for starch and amylopectin whereas HaAmy1 had higher catalytic efficiency. HaAmy1 and HaAmy2 were inhibited to the same magnitude by a synthetic amylase inhibitor (acarbose) while wheat amylase inhibitor showed about 2-fold higher inhibition of HaAmy1 than HaAmy2 at pH 7 while 6-fold difference at pH 11. Interactions of HaAmy1 and HaAmy2 with wheat amylase inhibitor revealed 2:1 stoichiometric ratio and much more complex interaction with HaAmy1. Conclusions: The diversity of amylases in perspective of their biochemical and biophysical properties, and their differential interactions with amylase inhibitors signify the potential role of these enzymes in adaptation of H. armigera on diverse plant diets. General significance: Characterization of digestive enzymes of H. armigera provides the molecular basis for the polyphagous nature and thus could assist in designing future strategies for the insect control. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: alpha-amylases; Amylase inhibitors; Digestive enzymes; Enzyme activity; Helicoverpa armigera